AN OVERVIEW ON USAGE OF NANOSCALE ZERO VALENT IRON FOR PHARMACEUTICALS ELIMINATION - Hanay, Özge; Türk, Hande (My University, 2019)
Pharmaceutically active compounds are gaining the recognition of emerging environmental contaminants classified as recalcitrantbio-accumulative compounds hence they are regarded as toxic and hazardous chemicals. In this context, efficient treatmentprocesses are needed. Nanotechnology can adequately address many of the water quality issues by using different typesnanomaterials. Nano zero valent iron (nZVI) has been applied to remove various organic compounds from aqueous solutionssince the removal mechanism depends on adsorption and degradation. This article summarizes the recent knowledge of nZVI inpharmaceutical degradation considering the key factors such as initial contaminant concentration, dosage of bare and modifiednZVI, pH of aqueous matrix and reaction time which are mainly examined in the experiments. Additionally, the degradationmechanism of studied pharmaceutical compounds monitored by observing intermediates and end-products is presented.
Keywords: Nanobilim ve Nanoteknoloji; Halk ve Çevre Sağlığı; Kimya; Tıbbi; Biyoteknoloji ve Uygulamalı Mikrobiyoloji; Çevre Bilimleri; Çevre Mühendisliği